Sanaungulus ruicheni (Hsiao & Huang, 2018) n. comb. with the differential diagnosis of genera Sanaungulus Fanti, Damgaard & Ellenberger, 2018 and Ornatomalthinus Poinar & Fanti, 2016 - Fanti, Fabrizio (Zootaxa, 2018)
Recently, Hsiao & Huang (2018) presented a taxonomical revision of Ornatomalthinus Poinar & Fanti, 2016 based on the discovery of a new species (O. ruicheni) from the Cretaceous Burmese amber of the Hukawng Valley (Myanmar). According to the authors, this species shows many differences in respect to O. elvirae Poinar & Fanti, 2016. I propose that due to these morphological divergences the new species cannot belong to the genus Ornatomalthinus (type-species O. elvirae) as indicated by Hsiao & Huang (2018). The appearance is in fact identical to Sanaungulus Fanti, Damgaard & Ellenberger, 2018 (Poinar & Fanti, 2016; Fanti et al., 2018). Additionally, Ornatomalthinus should remain in the subfamily Cantharinae. In this note the common characters of O. ruicheni and the criticalities of attribution to Ornatomalthinus are highlighted, a new combination is proposed and higher classification is discussed.